TEACHING ENGLISH USING ICE BREAKING TO TAIWANESE STUDENTS: EFL TEACHER’S EXPERIENCES - Khoirunnisaa', Try Ammalia; Asnas, Sania Alinda Mouli; Heriyawati, Dwi Fita (English Review: Journal of English Education, 2024)
This research examined the challenge, strategy, advantages, and disadvantage of using icebreakers when learning English among Taiwanese students. This research used narrative inquiry as its research design. Data collection was done through interviews conducted with an EFL teacher who was completing a doctoral program in Taiwan. Data analysis included identifying key themes from interview data. The research results stated that the use of ice breaking has challenges, strategies, advantages, and disadvantages when learning in class. The challenge was that students felt bored when the teacher used the same type of icebreaker over and over again. The strategy was to use technology-based icebreakers. The advantage was that it could improve a conducive learning environment. The disadvantage was that teachers had to have various types of icebreakers. This research underlines the complexities of employing icebreakers in English language instruction, as well as the significance of continued efforts, teacher flexibility, and creative variation to accommodate students' particular needs. In conclusion, a balanced and thoughtful approach to using icebreakers is critical to fostering a successful enjoyable classroom for Taiwanese students